2007
DOI: 10.1158/0008-5472.can-07-5185
|View full text |Cite
|
Sign up to set email alerts
|

ERK-Dependent MKP-1–Mediated Cisplatin Resistance in Human Ovarian Cancer Cells

Abstract: Mitogen-activated protein kinase (MAPK) phosphatase-1 (MKP-1) is the MAPK phosphatase family member that negatively regulates MAPK signaling. Our previous study showed that MKP-1 is involved in cisplatin resistance, but the mechanism underlying its resistance is not understood. Here, we show that ERK2-mediated MKP-1 expression is critical for cisplatin resistance. Specifically, we showed that in the human ovarian cancer cell lines, cisplatin induces MKP-1 through phosphorylation. We also showed that inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 37 publications
(56 reference statements)
11
100
1
Order By: Relevance
“…Fig. 3A shows that cisplatin treatment caused phosphorylation of ERK, p38, and c-Jun N-terminal kinases (JNK) and their downstream targets including CREB, and c-Jun, confirming our previous study showing that cisplatin activates all three major MAPK path- ways (26). Next, we determined which MAPK is responsible for cisplatin-induced autophagy.…”
Section: Elevation Of the Lc3-ii Level Is Correlated With Cisplatin Rsupporting
confidence: 85%
See 2 more Smart Citations
“…Fig. 3A shows that cisplatin treatment caused phosphorylation of ERK, p38, and c-Jun N-terminal kinases (JNK) and their downstream targets including CREB, and c-Jun, confirming our previous study showing that cisplatin activates all three major MAPK path- ways (26). Next, we determined which MAPK is responsible for cisplatin-induced autophagy.…”
Section: Elevation Of the Lc3-ii Level Is Correlated With Cisplatin Rsupporting
confidence: 85%
“…Cell Lines and Culture Conditions-Human ovarian cancer cell lines RMG-1, OV90, OV433, OVCA420, and CAOV3 were maintained as described previously (26). Immortalized human ovarian surface epithelial IOSE385 cells were obtained from Dr. Nelly Auersperg (University of British Columbia, Vancouver, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We included cisplatin in this experiment because our previous study showed that cisplatin treatment leads to increased MKP-1 protein levels and activates MAPKs. 27 Our purpose for using cisplatin treatment is to determine whether MKP-2 plays a role in the presence of DNA damage since cisplatin is a DNA damaging agent. In addition, we showed that both wild-type and S386A/ S391A mutant MKP-2 are potent inhibitors of ERK.…”
Section: Mkp-2 Is Phosphorylated In Vitro and Phosphorylation Of Mkp-mentioning
confidence: 99%
“…The molecular mechanism underlying MKP-1-mediated resistance to anti-cancer drugs is in part due to the activation of JNK-driven apoptosis by several anti-tumour agents such as anthracyclines, taxanes, cisplatin, proteasome inhibitors and more recently anti-EGFR drugs. High levels of MKP-1 inhibit JNK and counterbalance the cytotoxic effects of such drugs (Sanchez-Perez et al, 1998Small et al, 2004Small et al, , 2007Wang et al, 2006Wang et al, , 2007Workman and de Bono, 2008;Rojo et al, 2009). With respect to anti-EGFR therapy, in vitro results with the anti-EGFR drug AG1478 showed that MKP-1-modulated JNK activation was critical for drug-induced apoptosis.…”
mentioning
confidence: 99%